Decorating fiber nanotip with single perovskite quantum dot and other luminescent nanocrystals synthesized in oil-phase. (23rd October 2017) - Qian, Yu; Xing, Xing; Xu, Ya; Lu, Zhenda; Zhang, Weihua
Abstract: We report a simple yet robust method for fabricating single perovskite quantum dot (QD) decorated fiber nanotips. In this method, a single QD is directly picked up and subsequently glued on the apex of a specially fabricated cantilever fiber tip with a high success rate (approx. 70%) without using expensive close-loop feedback systems. Thanks to the flexibility and robustness of the fiber tips, no damage of the tips was observed in the process. Moreover, nanocrystal (NC) dispersing technique was developed to avoid undesired aggregations of QDs, and it guarantees that only one QD is glued each time. Finally, we demonstrate that this technique can also be applied to other oil-phase synthesized NCs, including CdSe QDs and upconversion luminescent NCs. It leads to many important applications on probing the local environment using high performance luminescent nanoprobes.